Integration of Shariah Audit and Shariah Governance in Supporting ESG Compliance: A Systematic Literature Review - Susi Astuti; Arief Rahman; Hendi Yogi Prabowo (Politeknik Ganesha Medan, 2026)
The growing global attention to Environmental, Social, and Governance (ESG) practices has prompted Islamic financial institutions to strengthen governance systems and oversight mechanisms oriented toward sustainability. Within the context of Islamic finance, ESG principles exhibit normative alignment with Shariah values, particularly the objectives of maqasid al-shariah, which emphasize justice, public interest (maslahah), and accountability. Nevertheless, studies that comprehensively integrate the roles of Shariah Audit and Shariah Governance in supporting ESG compliance have largely evolved in parallel and have not yet been systematically synthesized in the literature.This study aims to synthesize the contributions of Shariah audit and Shariah governance in promoting ESG compliance within Islamic financial institutions, while also identifying existing conceptual, methodological, and implementation gaps. A systematic literature review was employed, guided by the PRISMA framework, covering 162 articles retrieved from the Scopus database. The selected studies were analyzed using thematic synthesis combined with bibliometric mapping to identify dominant themes, conceptual patterns, and trajectories of research development.The findings indicate that Shariah governance serves as a primary foundation for strengthening ESG compliance, particularly through oversight mechanisms, transparency, and accountability that exert a significant influence on the social and governance dimensions. Meanwhile, Shariah audit especially risk-based internal audit and integrated audit models—contributes to enhancing credibility and assurance functions. However, its role in the ESG context remains relatively limited and faces challenges related to auditor competencies and the lack of standardization. The conceptual integration of maqasid al-shariah and ESG principles is also viewed as a promising ethical governance paradigm, yet it has not been fully translated into applicable operational frameworks.Overall, this study underscores the strategic role of Shariah audit and Shariah governance in advancing ESG compliance within Islamic financial institutions, while revealing regulatory, methodological, and implementation gaps that warrant further attention. The findings highlight the importance of developing more standardized frameworks, strengthening human capital capacity, and expanding empirical validation to optimize the effectiveness of Shariah audit and align Islamic financial practices with global sustainability standards